Climate change adaptability: the economic efficacy of investing in irrigation in Chivi Rural District, Zimbabwe:paper presented at a conference held on the 14th-16th July 2015, Elephant Hills Resort, Victoria Fallls, Zimbabwe - Matunhu, Jephias (Midlands State University, 2016)
Theme: 1st International Research Conference On Driving Socio-Economic Development Through Value Addition And Sustainable Use Of Resources